Stability of Amphotericin B in Fungal Culture Media - Cheung, S. C. (1975)
We have found that amphotericin B is unstable in two commonly employed fungal culture media. This instability leads to inaccuracies in determining the actual level of susceptibility of slow-growing strains that require prolonged incubation for growth. To help compensate for this problem, we have described two rapid methods of susceptibility testing.